2016
DOI: 10.1080/08870446.2016.1167209
|View full text |Cite
|
Sign up to set email alerts
|

Statistically modelling the relationships between Type D personality and social support, health behaviors and symptom severity in chronic illness groups

Abstract: Objective: The study aimed to develop a predictive model of how Type D personality influences health behaviors, social support, and symptom severity and assess its generalizability to a range of chronic illnesses. Design: Participants were classified as either healthy (n = 182) or having a chronic illness (n = 207). Participants completed an online survey measuring Type D and a range of health-related variables. Chronic illness participants were classified as having either a functional somatic syndrome (i.e. c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Categorical Type D was also only able to improve prediction, albeit modestly, for one of the four outcomes, over and above continuous subscales. Consistent with past research (Atherton et al, 2014;Horwood et al, 2016;Kelly-Hughes et al, 2014), results also showed no evidence of interactive effects of negative affectivity and social inhibition. Thus, while interactive effects are one means of personality types providing superior prediction to interval scales (Asendorpf, 2003), this does not appear to be the case when using either the interaction of interval subscales or when using categorical Type D.…”
Section: Assumptions Of Type Dsupporting
confidence: 79%
See 4 more Smart Citations
“…Categorical Type D was also only able to improve prediction, albeit modestly, for one of the four outcomes, over and above continuous subscales. Consistent with past research (Atherton et al, 2014;Horwood et al, 2016;Kelly-Hughes et al, 2014), results also showed no evidence of interactive effects of negative affectivity and social inhibition. Thus, while interactive effects are one means of personality types providing superior prediction to interval scales (Asendorpf, 2003), this does not appear to be the case when using either the interaction of interval subscales or when using categorical Type D.…”
Section: Assumptions Of Type Dsupporting
confidence: 79%
“…Research shows that dichotmizing an interval scale reduces correlations (Aguinis, Pierce, & Culpepper, 2009;Rucker, McShane, & Preacher, 2015). Demonstrating this general point, Horwood et al (2016) found that treating Type D as a dichotomous variable reduced predictive validity relative to a continuous representation of Type D.…”
Section: Challenges To the Assumptions Underpinning Type D Personalitymentioning
confidence: 95%
See 3 more Smart Citations